A modified echocardiographic approach improves reliability of superior vena caval flow quantification. Issue 1 (26th May 2016) - Ficial, Benjamim; Bonafiglia, Elena; Padovani, Ezio M; Prioli, Maria A; Finnemore, Anna E; Cox, David J; Broadhouse, Kathryn M; Price, Anthony N; Durighel, Giuliana; Groves, Alan M
Abstract : Objective: To assess accuracy and repeatability of a modified echocardiographic approach to quantify superior vena cava (SVC) flow volume that uses a short-axis view to directly measure SVC area and a suprasternal view to measure flow velocity, both at the level of the right pulmonary artery. Setting: Three tertiary-level neonatal intensive care units. Design: This was a multicentre, prospective, observational study. Accuracy of the traditional and modified approach was first assessed by comparing echo measurements according to both techniques with Phase contrast MRI (PCMRI) assessments, in a cohort of 10 neonates. In a second cohort of 40 neonates, intraobserver scan–rescan repeatability and interobserver analysis–reanalysis repeatability were assessed by repeated SVC flow echo measurements, according to both techniques. Results: The traditional echocardiographic approach to assessment of SVC flow had a moderate agreement with PCMRI (r 2 0.259), a scan–rescan intraobserver repeatability index (RI) of 37% (limits of agreement (LOA) −47/+51 mL/kg/min) and an interobserver analysis–reanalysis RI of 31% (LOA −38/+40 mL/kg/min). The modified approach showed a stronger agreement with PCMRI (r 2 0.775), an improved intraobserver scan–rescan repeatability (RI 22%, LOA −24/+18 mL/kg/min) and improved interobserver analysis–reanalysis repeatability (RI 18%, LOA −18/+20 mL/kg/min). Conclusions: Echocardiographic assessment of SVC flow volume by tracing area from a short-axis view and measuring velocity–time integral from a suprasternal view offered an improvement in accuracy and repeatability, building on the traditional approach previously described.